2012
DOI: 10.1111/j.1523-5378.2011.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta‐Analysis: Helicobacter pylori Eradication Therapy After Simple Closure of Perforated Duodenal Ulcer

Abstract: Helicobacter pylori eradication after simple closure of duodenal ulcer perforation gives better result than the operation plus antisecretory non-eradication therapy for prevention of ulcer recurrence. All duodenal ulcer perforation patients should be tested for H. pylori infection, and eradication therapy is required in all infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…Comment: Almost all reports are in concordance for eradication after gastric preserving surgery [152]. There is no agreement about eradication after distal gastrectomy.…”
Section: Surgical Treatmentmentioning
confidence: 86%
“…Comment: Almost all reports are in concordance for eradication after gastric preserving surgery [152]. There is no agreement about eradication after distal gastrectomy.…”
Section: Surgical Treatmentmentioning
confidence: 86%
“…Indeed, evidence from a systematic review and meta-analysis of this approach has suggested empirical treatment with H. pylori eradication therapy is superior to antisecretory treatment alone 10. Other risk factors such as hypersecretory states should also be sought and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic simple closure operations for peptic ulcer perforation are now widely accepted worldwide, favoring the less-invasive simple closure technique with postoperative H. pylori eradication. A systematic review and meta-analysis of patients with duodenal ulcer perforation compared the simple closure method plus postoperative H. pylori eradication therapy to simple closure and antisecretory noneradication therapy, showing that H. pylori eradication after simple closure of duodenal ulcer perforation provided better results than the operation plus antisecretory noneradication therapy for preventing ulcer recurrence [8]. The Maastricht III and the newest Maastricht IV Consensus Report guidelines recommended bacterial eradication in infected patients presenting with ulcer complications [9,10].…”
Section: Peptic Ulcer Diseasementioning
confidence: 99%